Efterkrigsritualet – En komparativ analyse af de danske krigsbytteofringer - Thulstrup, Pernille Mosholm Boye (Kuml, 2013)
The post-war ritual – a comparative analysis of the Danish war booty offerings and the Roman triumphs This article is inspired by a theory, which postulates that the Roman triumphs should be seen as an inspirational source relative to the interpretation of war booty offerings found in Danish bogs, and aims to examine the validity of this claim. The so-called triumph theory originates in the discussion of whether the military equipment recovered from Danish bogs stems from defensive or offensive battles. According to the triumph theory, the war booty was brought home from battles fought in foreign parts by a victorious Germanic people. It was then was placed in a triumph procession, following the Roman model, with display of the booty, and finally sacrificed in a lake according to traditional Germanic custom. After a general introduction to the Roman triumphs (fig. 1) and the Danish war booty offerings (fig. 2), some of the elements making up these two ceremonies are presented, specifically the actual material war booty, the human captives and the animals (figs. 4-5). There are distinct differences between the two ceremonies, for example in the war booty included in the Roman triumphs (fig. 3) and the Germanic war booty offerings, respectively. One discrepancy, which is difficult to ignore, is the treatment of, and further potential for reuse of, the captured weapons of the enemy displayed in the two ceremonies. There are examples where booty from the Romans’ triumphs was later reused. This could not be the case for the Germanic war booty offerings, whereby weapons underwent such a massive process of destruction and, furthermore, were then deposited in lakes, making reuse seem impossible. The locations where the respective ceremonies took place – the city of Rome and South Scandinavian lakes – are then presented. An alternative explanation for the war booty offerings is then examined. Instead of seeing them as a Germanic version of the Roman triumphs, could the offerings be interpreted as Roman victory trophies (fig. 6)? This idea is rejected due to the lack of evidence for the sites of the offerings also being that of the actual battle field. Finally, attention is turned to the classical writers, who wrote about the Germanic and Gallic custom of depositing of military equipment, in order to extract what they can say about the gods whom the two ceremonies were intended to benefit. In the conclusion, the arguments are summed up in support of the author’s view that the triumph theory does not provide a convincing explanation for the Danish war booty offerings. Pernille Mosholm Boye Thulstrup Forhistorisk Arkæologi Institut for Kultur og Samfund Aarhus Universitet